2022
DOI: 10.1371/journal.pone.0273831
|View full text |Cite
|
Sign up to set email alerts
|

Surgery duration: Optimized prediction and causality analysis

Abstract: Accurate estimation of duration of surgery (DOS) can lead to cost-effective utilization of surgical staff and operating rooms and decrease patients’ waiting time. In this study, we present a supervised DOS nonlinear regression prediction model whose accuracy outperforms earlier results. In addition, unlike previous studies, we identify the features that influence DOS prediction. Further, in difference from others, we study the causal relationship between the feature set and DOS. The feature sets used in prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…Our additional subgroup analysis, stratified by surgery type, further highlights the significant influence of sample size on model performance. We also acknowledge that other studies in the literature have reported similar findings, with narrow differences among various ML models in terms of MAE and RMSE 15 , 16 , 33 . Predicting operative time is inherently complex, involving numerous potential factors, many of which may be challenging to quantify in large databases 41 , 42 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our additional subgroup analysis, stratified by surgery type, further highlights the significant influence of sample size on model performance. We also acknowledge that other studies in the literature have reported similar findings, with narrow differences among various ML models in terms of MAE and RMSE 15 , 16 , 33 . Predicting operative time is inherently complex, involving numerous potential factors, many of which may be challenging to quantify in large databases 41 , 42 .…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, previous studies have shown that boosted trees outperform other models in predicting operative times. A previous study conducted in Israel reported that GBT performed best in predicting the operative time for eight surgery types, with the lowest MAE and RMSE among RF, GBT, and multilayer perception 16 . Another study in the United States also reported that the boosted regression tree performed best in predicting the operative time for robot-assisted surgery, with the lowest RMSE among multivariable linear regression, ridge regression, lasso regression, RF, boosted regression tree, and neural network 33 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Тривалий час хірургічного втручання може посилити маніпуляції з тканинами та травму, що призведе до посилення запальних реакцій і сповільненого загоєння ран [7]. Мінімізація тривалості хірургічного втручання за допомогою ефективних методів і інструментів може допомогти зменшити ці ризики та зменшити ймовірність утворення надмірного рубця [8].…”
Section: Sutureless Sclerotomy In Patients After Retinal Detachment A...unclassified